Comparison of Road Traffic Noise at Residential Areas in Klang Valley, Selangor and Nibong Tebal, Penang - Mohamad Nor, Nur Atiqah (International Journal of Integrated Engineering, 2019)
In this work, weekdays and weekends noise level were investigated in three residential areas in high density population residential areas and three medium density population residential areas. The objective of this study is to investigate the level of traffic noise at the selected residential areas. Noise level was measured using sound level meter over a range of traffic noise levels. The results revealed that the highest noise levels measured were at Desa Tun Razak in Klang Valley with 74 .25 dB(A) in the morning, 74.14 dB(A) in the evening and 73.18 dB(A) at night. Â The lowest LAeq was measured at Taman Ilmu Indah with the noise levels of 62.9 dB(A) in the morning, 66.3 dB(A) in the evening and 62 dB(A) at night. The high noise pollution levels in the morning and evening at study areas locations were due to morning rushing hours of ofï¬ce workers and business men and women, e.g. resuming work at ofï¬ces and opening shops for customers. Noise generated from motorcycles are generally noticeable and contribute to the high value of Lmax. All the recorded noise levels on peak hours and off peak hours exceeded the guidelines for maximum permissible sound level (LAeq) for residential (high density and medium density) areas during daytime (from 7.00 am to 10.00 pm) are 60 dB (A) (high density), 55 dB(A) (medium density) and the night-time (10.00 pm to 7.00 am) are 50 dB(A) (high density), 45 dB(A) (medium density).